Concept of Learning Evaluastion of Islamic Religious Education Courses in Public Universities From The Perspective of Syed Muhammad Naquib al- Attas - Mahardika Putera Emas, Mahardika Putera Emas; Ismail; Nurhilaliati (EDUCAN : JURNAL PENDIDIKAN ISLAM, 2024)
The background of this research is the issue of PAI courses at public university which is still inadequate. It is felt the determination of PAI courses as national compulsary courses is still not sufficient to achieve its objective or national educational goals. Insufficient study hours, material that still tends to be descriptive, and not beng able to answer student’s personal needs ultimately become a scourge when conducting learning evaluations. Milieu of public university, which differ drastically then lower levels, requiere an appropriate evaluation model. Syed Muhammad Naquib al-Attas, as world-class thinker from Malaysia, has a number of unique educational ideas that can be inspiration, incluidng in terms of evaluation. Moreover, he has directly led a higher education institution which has become a reference for many universities to this day. This research aims to elaborate on the concept of al-Attas learning evaluation in the context of PAI courses at public university. This reasearch shows the the evaluation philosophy and practice carried out by al-Attas could become milestone for reforming the principles and practices of  PAI courses at public university, especially in terms of learning evaluation. In order to achieve its objectives, this research uses a library research method, by examining the relevant primary and secondary sources.